Irisin in Type 2 Diabetes and Obesity: A Biomarker of Metabolic and Lipid Dysregulation - Sanja Stanković; Valentina V. Nikolić; Nikola Krstić (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Studies suggested irisin’s involvement in insulin sensitivity, conversion of white adipose tissue into brown which is more metabolically active. Studies have been shown negative correlation of irisin levels with presence of diabetes mellitus (DM). Association of irisin levels with body mass index (BMI) and lipid profile could be useful in monitoring metabolic disorders and potential complications in DM. Methods: This cross-sectional study enrolled patients which were divided in 3 groups based on diabetes status and BMI: participants without DM, patients with DM, and a normal BMI (<25 kg/m²) and patients with DM and an increased BMI (⩾25 kg/m²). Irisin levels were measured from blood samples and correlation was made with parameters of lipid profile. We wanted to find differences in irisin concentration in comparing groups and to examine the correlation of irisin and metabolic parameters. The relationships between irisin levels and metabolic parameters, including lipid profile and the triglyceride-glucose (TyG) index, were assessed using Pearson’s, and Spearman’s correlation analysis, depending on data distribution. Results: Irisin levels were significantly lower in patients with DM compared to non-diabetic individuals, regardless to BMI (patients without diabetes: median 25.47 ng/ml, IQR (22.27-27.54), with diabetes and BMI < 25 kg/m²: 22.16 ng/ml, IQR (19.29-23.76) and patients with diabetes and BMI ⩾ 25 kg/m²: mean ± SD (21.77 ± 5.72) ng/ml, P  = .004). Additionally, we report a 1.15-fold decrease in irisin levels in group with diabetes, and BMI < 25 kg/m² compared to non-diabetic individuals and a 1.18-fold decrease in group with diabetes and BMI ⩾ 25 kg/m² compared to non-diabetic individuals. Additionally, lower irisin levels were correlated with higher triglycerides ( r  = −.343, P  = .024), lower HDL cholesterol ( r  = .363, P  = .017), and higher TyG index ( r  = −.315, P  = .04), indicating a potential link between irisin and metabolic dysregulation. No significant association was observed between irisin levels and BMI. Conclusion: Our findings suggest that irisin may serve as a biomarker for monitoring metabolic dysregulation in diabetes, particularly in relation to lipid metabolism and insulin resistance. Further research is needed to clarify its role in metabolic disease progression and potential therapeutic implications.